MORPHOMETRIC PARAMETERS OF CARDIO-MYOCYTES IN ISCHEMIC HEART FAILURE UNDER TREATMENT BY IVABRADINE - Федоров, С.В.; Геращенко, С.Б. (World of Medicine and Biology, 2014)
With the aim of evaluation of effects of ivabradine for cardiomyocytes status we made the ischemic model of heart failure in mature 30 rats (Rattus Norvegicus L.). By morphometric investigation the decrease of average parameter of cells’ sectional area, average parameter of nuclear area and inhibition of connective tissue growth were observed in animals with additional usage of ivabradine. Thus, ivabradine showed the middle positive effect for myocardium what was presented by decrease of cells and their nuclei hypertrophy, parenchyma dystrophy and fibrosis of heart muscle.
Keywords: heart failure; Ivabradine; myocardium morphology